SPIRITUAL LEARNING AS A WAY TO ACHIEVE RELIGIOUS MODERATION - Ratno; Syahri, Akhmad (Universitas Islam Negeri Mataram, 2024)
Amid the dynamics of modern life, the challenge of maintaining a balance between spiritual and material life is increasingly urgent because many people are not aware of and understand themselves, so they violate the norms and values that exist in society. This article outlines the concept and benefits of spiritual learning to realize religious moderation by using a qualitative method, the type of literature study. This research reveals that: Religious moderation is an approach that offers a wise middle ground for incorporating spiritual values into daily life in harmony. In this case, spiritual learning that can be applied to realizing religious moderation is through inner exercises, such as meditation and praying before doing activities; physical exercises, both verbal and non-verbal; education and learning in schools, such as the creation of meaning through the integration of value theory, religious theory, and scientific theory based on metaphysical questions in spiritual-based learning and experience. This is beneficial for building higher self-awareness about oneself, society, and God. and can develop a good attitude in Tawazzun, I'tidal, Tasamuh, Tawassuth, Shura, Ishlah, Tahadhdhur, Musawah, Aulawiyah, Tathawwur and Ibtikar. This research shows that to build one's self-awareness, there is a need for a learning process that integrates spiritual values and religious moderation in daily life.